Seven Cool Number Patterns - Karim, Mohammed (Discoveries in Agriculture and Food Sciences, 2017)
Inspired by a number pattern found while reading an online newspaper seven number patterns are created. Behind each pattern there is a distinct algorithm. Some of these patterns are a sequence of a single or double digit, and the rest are packing ups of one or two digits either one or both sides of a particular number. An interpretation of the inspiring number pattern is also provided.